Control of optical transport parameters of 'porous medium – supercritical fluid' systems. (30th November 2015) - Zimnyakov, D A; Ushakova, O V; Yuvchenko, S A; Bagratashvili, V N
Abstract: The possibility of controlling optical transport parameters (in particular, transport scattering coefficient) of porous systems based on polymer fibres, saturated with carbon dioxide in different phase states (gaseous, liquid and supercritical) has been experimentally studied. An increase in the pressure of the saturating medium leads to a rise of its refractive index and, correspondingly, the diffuse-transmission coefficient of the system due to the decrease in the transport scattering coefficient. It is shown that, in the case of subcritical saturating carbon dioxide, the small-angle diffuse transmission of probed porous layers at pressures close to the saturated vapour pressure is determined by the effect of capillary condensation in pores. The immersion effect in 'porous medium – supercritical fluid' systems, where the fluid pressure is used as a control parameter, is considered. The results of reconstructing the values of transport scattering coefficient of probed layers for different refractive indices of a saturating fluid are presented.